The Inclusion of Habits of Mind in Biology Textbook for 9th Grade in Jordan of According to Project 2061 - AL-Qashi, Yousef; Khataibeh, Abdullah (Jordan Journal of Educational Sciences, 2019)
This study aimed at detecting the degree to which the biology textbook for 9th grade in Jordan included the habits of mind, according to project 2061. To achieve this aim, a tool was developed for the analysis of the five main habits of mind that emerged from the AAAS Project (2061): values and attitudes, computation and estimation, manipulation and observation, communication skills, and critical response skills. The researchers used frequencies and percentages in statistical processing, the paragraph was used as a unit of analysis. The number of paragraphs analyzed was (988). The results showed an imbalance in the inclusion of habits of mind in the biology textbook: The "communication skills" responded by a large percentage (61%) compared to other habits, "values and attitudes" by an average percentage (26%), "manipulation and observation" by a small percentage (11%), "critical response skills" by very little percentage (2%), and the textbook does not include the habit of "calculation and appreciation" (0%). It was recommended that authors should have an emphasis on the equiponderant inclusion of habits of mind in science textbooks